Synergistic effects of methyl 2-cyano-3,11-dioxo-18beta-olean-1,-12-dien-30-oate and erlotinib on erlotinib-resistant non-small cell lung cancer cells - Ebony Nottingham; Elizabeth Mazzio; Sunil Kumar Surapaneni; Shallu Kutlehria; Arindam Mondal; Ramesh Badisa; Stephen Safe; Arun K. Rishi; Mandip Singh (Elsevier, 2021)
Non-small cell lung cancer (NSCLC) is often characterized by an underlying mutation in the epidermal growth factor receptor (EGFR), contributing to aggressive metastatic disease. Methyl 2-cyano-3,11-dioxo-18beta-olean-1,12-dien-30-oate (CDODA-Me), a glycyrrhetinic acid derivative, reportedly improves the therapeutic response to erlotinib (ERL), an EGFR tyrosine kinase inhibitor. In the present study, we performed a series of studies to demonstrate the efficacy of CDODA-Me (2 μM) in sensitizing HCC827R (ERL-resistant) cells to ERL. Herein, we first established the selectivity of ERL-induced drug resistance in the HCC827R cells, which was sensitized when ERL was combined with CDODA-Me (2 μM), shifting the IC50 from 23.48 μM to 5.46 μM. Subsequently, whole transcriptomic microarray expression data demonstrated that the combination of ERL + CDODA-Me elicited 210 downregulated genes (0.44% of the whole transcriptome (WT)) and 174 upregulated genes (0.36% of the WT), of which approximately 80% were unique to the ERL + CDODA-Me group. Synergistic effects centered on losses to cell cycle progression transcripts, a reduction of minichromosome maintenance complex components (MCM2-7), all key components of the Cdc45·MCM2-7GINS (CMG) complex, and replicative helicases; these effects were tantamount to the upregulation of processes associated with the nuclear factor erythroid 2 like 2 translational response to oxidative stress, including sulfiredoxin 1, heme oxygenase 1, and stress-induced growth inhibitor 1. Collectively, these findings indicate that the synergistic therapeutic effects of ERL + CDODA-Me on resistant NSCLC cells are mediated via the inhibition of mitosis and induction of oxidative stress.